The Influence of Environmental Consciousness, Environmental Concern, Perceived Value, Perceived Risk on Purchase Intention Through Product Trust Mediation: Study of the Recycled Product Industry in Banten Province - An Nisaa Syauqi Ul Jannah; Prio Utomo; Florentina Kurniasari (Journal Research of Social Science, Economics, and Management, 2024)
The waste problem requires a multidimensional approach, especially in processing and sorting at the source, in line with the Sustainable Development Goals of achieving zero waste in the future. The waste bank program has been introduced to support waste reduction and the circular economy, but public interest in recycled products remains low. Banten Province, one of the five provinces with the highest waste tonnage in Indonesia in 2022, showed interest of only 19.3%. This study aims to identify the factors influencing public purchase intention of recycled products, with product trust as a mediating variable. Through online questionnaires and data analysis using SEM PLS, involving 158 respondents in Banten Province, it was found that environmental consciousness, environmental concern, perceived value, and perceived risk significantly influence the purchase intention of recycled products. Additionally, these factors also significantly affect product trust. Mediation analysis shows that product trust can mediate the relationship between environmental consciousness and environmental concern with purchase intention, but it is not optimal in mediating the impact of perceived value and perceived risk. Recommendations for environmental activists in Banten Province include increasing the credibility and clarity of information regarding recycled products, as well as ensuring the cleanliness and safety of these products to directly enhance public purchase intention and support the circular economy in Banten Province.